2017
DOI: 10.15376/biores.12.3.4912-4925
|View full text |Cite
|
Sign up to set email alerts
|

Renewable Material-derived Biochars for the Efficient Removal of 2,4-Dichlorophen from Aqueous Solution: Adsorption/Desorption Mechanisms

Abstract: This study investigated the efficiency of peanut hull (PBC), bush branch (BBC), Spartina alterniflora (SBC), and rape straw (RBC) in removing 2,4-dichlorophen (2,4-DCP) from an aqueous solution. The 2,4-DCP removal efficiency of the four kinds of biochars (BCs) increased in the order BBC > PBC > SBC > RBC. The adsorption process was affected by the pH, contact time, temperature, BC's particle size, and dosage. Based on the results of Fourier transform infrared spectrometry (FTIR) and scanning electron microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…The XPS data also show functional groups of biochar C1s, i.e., C-C (284.8 eV), C-O (286.1 eV), and C=O (287.0 eV), and four peaks for the O1s were C=O at 532.5 eV, O-H at 530.3 eV, O-C=O at 532.8 eV, and C-OO at 533.8 eV. The above data support the fact that biochar contains abundant oxygen-containing functional groups, as shown by our research group in the past [50]. Sanchez-Hernandez [51] showed that biochar can inactivate metabolites of organophosphorus pesticides, which they mainly attributed to the abundant functional groups in biochar.…”
Section: Functional-group Characteristics Of Raw Biochar and Soilsupporting
confidence: 87%
“…The XPS data also show functional groups of biochar C1s, i.e., C-C (284.8 eV), C-O (286.1 eV), and C=O (287.0 eV), and four peaks for the O1s were C=O at 532.5 eV, O-H at 530.3 eV, O-C=O at 532.8 eV, and C-OO at 533.8 eV. The above data support the fact that biochar contains abundant oxygen-containing functional groups, as shown by our research group in the past [50]. Sanchez-Hernandez [51] showed that biochar can inactivate metabolites of organophosphorus pesticides, which they mainly attributed to the abundant functional groups in biochar.…”
Section: Functional-group Characteristics Of Raw Biochar and Soilsupporting
confidence: 87%
“…The 2,4,6-TCP solution and biochars were mixed in a 100 mL glass flask, and sealed with tape and shaken at 180 rpm for 2 h in a water bath at 25 °C, 35 °C, and 45 °C. The background electrolyte of the mixed solution was 0.01 mol L −1 NaNO 3 , and the pH was adjusted with 0.1 M NaOH or HCl 22 . After reaching the equilibrium during the sorption experiment, the solution was filtered through 0.22 μm nylon membrane.…”
Section: Methodsmentioning
confidence: 99%
“…The column temperature was initially 80 °C for 1 min, and then it increased to 350 °C at a rate of 10 °C/min. The carrier gas was helium at a flow rate of 1 mL/min, and the injection volume was 1 µL; the injector was operated in the split mode after sample injection (Cui et al 2017a).…”
Section: Characterization Of the Biochar Extract Solutionsmentioning
confidence: 99%